Posted by **Greg** on Wednesday, April 18, 2012 at 10:43pm.

Find the inverse of the following function:

f(x) = 3x + 12

I don't think I worked this problem off correctly...I am suppose to find the inverse of the function

Is this the correct way to work this problem?

y= 3x + 12

x= 3y + 12

3y = x - 12

f-1(x) = x - 12/3

- Algebra 2 -
**Anna**, Wednesday, April 18, 2012 at 11:30pm
You would divide everything by 3 leaving you with f-1(x)= x/3 - 4

- Algebra 2 -
**ashwni kumar**, Thursday, April 19, 2012 at 8:15am
see the correct and easy way is like this :

y=3x +12

now get x in terms of y

3x =y-12

or x= (y-12)/3

now replace x with y and vice versa

so you will get :

y= (x-12)/3

or f-1(x)= x/3 - 4

this should be the answer

## Answer This Question

## Related Questions

- College Algebra - Find the inverse of the function below. Graph the function ...
- algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...
- pre calculus - Find the inverse of the function below. Graph the function below ...
- Calculus, check my answers, please! 3 - Did I get these practice questions right...
- math - The cost of producing q articles is given by the function C=f(q)=100+2q...
- precalculus - Find the inverse of the function below. Graph the function below ...
- math - Could you show me step by step how to find the inverse of this problem: ...
- Calculus (Please check my work!) - Suppose that y = f(x) = x^2 - 4x + 4. Then on...
- Algebra - Myra uses an inverse variation function to model the data for the ...
- inverse - find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2...

More Related Questions